Financial fragility in open-ended mutual funds: The role of liquidity management tools - Peter G. Dunne; Lorenz Emter; Falko Fecht; Raffaele Giuliana; Oana Peia (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2023)
We study the role of liquidity management tools (LMTs) in mitigating financial fragility in investment funds during the COVID-19 market distress. We employ a unique dataset that reports the availability of different types of LMTs in a sample of Irish-domiciled corporate bond funds. We find that funds with access to price-based tools such as redemption fees or anti-dilution levies experienced lower net outflows in March 2020, as compared to funds with only quantity-based tools such as redemption gates, temporary suspensions or redemption in kind. This difference is stronger among funds with a high sensitivity of flows to past-performance and reflects both higher gross in- flows and lower gross outflows during this episode. Funds with price-based LMTs also rebalance their portfolios towards less liquid bonds, which results in lower price fragility among bonds held disproportionally by our sample of Irish-domiciled funds.
Keywords: G2; G23; 330; liquidity management tools; investment funds; COVID-19; financial fragility